Factors associated with early marriage - Putri, Yulita; Ketaren, Sinar Otniel; Bangun, Henny Arwina; Nababan, Donal; Manurung, Jasmen (Jurnal Prima Medika Sains, 2024)
Early marriage among adolescents is a significant social issue that is often linked to unintended pregnancies resulting from premarital sexual activity. This cross-sectional study aimed to identify the factors associated with early marriage among teenagers in Kelurahan Sari Rejo, Medan Polonia, Indonesia, from October 2023 to May 2024. A total of 65 early married adolescents aged 15-18 years were included in this study. The findings revealed that parental education, socioeconomic status, and parenting style were not significantly associated with early marriage. However, information source and peer influence were significant predictors. Adolescents who engaged in unhealthy peer relationships were 2.20 times more likely to marry early than those with healthy peer associations. These results underscore the importance of peer influence and the need for comprehensive sex education programs to address early marriages among teenagers.